2015
DOI: 10.1111/ggi.12610
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early rehabilitation on activities of daily living in patients with aspiration pneumonia

Abstract: The present results suggest that early rehabilitation might improve ADL during hospitalization in patients with aspiration pneumonia. Geriatr Gerontol Int 2016; 16: 1181-1187.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
0
26
1
Order By: Relevance
“…Yagi et al. showed that 71% of elderly AP patients with hospitalization‐associated disability did not have improved ADL scores during hospitalization 7. However, the study showed that early rehabilitation improved ADL significantly (odds ratio, 1.6; 95% confidence interval [CI], 1.5‐1.6).…”
Section: Methods and Resultsmentioning
confidence: 95%
“…Yagi et al. showed that 71% of elderly AP patients with hospitalization‐associated disability did not have improved ADL scores during hospitalization 7. However, the study showed that early rehabilitation improved ADL significantly (odds ratio, 1.6; 95% confidence interval [CI], 1.5‐1.6).…”
Section: Methods and Resultsmentioning
confidence: 95%
“…Early rehabilitation showed an effect in preventing decreased functional status in elderly aspiration pneumonia patients, but it also increased the length of hospital stay, simultaneously resulting in higher hospitalization costs 21 . Unfortunately, rehabilitation showed a limited effect in preventing decline of functional status in elderly CAP patients on propensity score analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of rehabilitation have been evaluated from various aspects, but there was no de nite conclusion. Some studies showed that early rehabilitation reduced LOS [15,16] in pneumonia, but another study showed that it would prolong LOS [7]. The effects of rehabilitation on mortality and readmission rates were also unclear [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased FS prolongs length of stay (LOS) in elderly CAP patients [5], and the prevalence of functional decline was reported to be 8.6%-20% in CAP [5,6]. Early rehabilitation therapy might improve activities of daily living (ADL) during hospitalization in patients with aspiration pneumonia, but it may increase LOS [7]. The effect of rehabilitation in preventing decreased FS in CAP has remained unclear.…”
Section: Introductionmentioning
confidence: 99%